Changes in the Guimarães visitors` profile and the city attributes perceptions in the post hosting of the 2012 European Capital of Culture - Paula Cristina Remoaldo; Laurentina Vareiro; José Cadima Ribeiro (Tourism & Management Studies)
The European Capitals of Culture (ECOC) are the most ambitious European cultural partnership project implemented in Europe, if one looks at its scale. In 2012, for the first time in Portugal, a medium sized city was its host. Guimarães (in the northwest of Portugal) was the city chosen. Three years after hosting the ECOC, it is time to assess what has changed as a consequence of hosting the event in terms of visitors’ profile and the perception of the city´s attributes. Primary data sources were used, gathered via conducting surveys on tourists in the ex-ante (2010/11) and post-event periods (2015) to Guimarães. Analytically, statistical methods were used putting in evidence the similarities and /or differences found regarding the visitors’ profiles and perceptions towards the destination´s attributes, when looking at the two time periods being analyzed. In relation to the results achieved, it was concluded that a change in the visitors’ profile to Guimarães took place (there was a more balance between men and women; a decrease in the amount of tourists aged from 0 to 25 and an increase in those aged from 46 to 65; as well as an increase in tourists with lower schooling levels), aside from a notorious evolution in what regards the perceived city attributes. One believes that the empirical results attained are a valuable source of information for tour operators and, mainly, for city planning and for the managing authorities.